2003
DOI: 10.1152/ajpheart.00106.2003
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive remote ischemic preconditioning for global protection of skeletal muscle against infarction

Abstract: The aim of this study was to investigate the efficacy and mechanism of action of a noninvasive remote ischemic preconditioning (IPC) technique for the protection of multiple distant skeletal muscles against ischemic necrosis (infarction). It was observed in the pig that three cycles of 10-min occlusion and reperfusion in a hindlimb by tourniquet application reduced the infarction of latissimus dorsi (LD), gracilis (GC), and rectus abdominis (RA) muscle flaps by 55%, 60%, and 55%, respectively, compared with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
155
1
4

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(166 citation statements)
references
References 43 publications
6
155
1
4
Order By: Relevance
“…The use of limbs is one of the most promising possibilities of evolving both pre-and postconditioning ischemic tolerance. 28,29 The major beneficiary of these approaches is the heart, 29 but the kidney, 30 distant muscle, 31 liver, 32 lung, 15 or CNS 33 can also be targeted. With respect to remote preconditioning, the present study has two messages.…”
Section: Discussionmentioning
confidence: 99%
“…The use of limbs is one of the most promising possibilities of evolving both pre-and postconditioning ischemic tolerance. 28,29 The major beneficiary of these approaches is the heart, 29 but the kidney, 30 distant muscle, 31 liver, 32 lung, 15 or CNS 33 can also be targeted. With respect to remote preconditioning, the present study has two messages.…”
Section: Discussionmentioning
confidence: 99%
“…This energy is provided by ATP molecules, for which storage is limited (ϳ35-55 mol/mg protein) (2,64,66).…”
Section: Mitochondria the "Powerhouse" Of The Cellsmentioning
confidence: 99%
“…Another potential explanation might be an improvement in metabolic efficiency via activation of KATP channels. In animal experiments, prolonged ischemia of the skeletal muscle demonstrates that IPC attenuates ATP depletion [50][51][52][53] , secondary to the activation of KATP channels [53][54][55][56][57] . Previous work showed that the activation of KATP channels may contribute to more effective blood flow redistribution during exercise 58,59) .…”
Section: Potential Factorsmentioning
confidence: 99%